Pure inorganic waxy active material as well as preparation method and application thereof

By chelating sodium polyphosphate with divalent cations, the pure inorganic wax-like co-doped polyphosphate material CoPPW is solved, and the problem of non-degradation and non-osteogenic effects of traditional wax materials is achieved, effectively stopping hemostatic in orthopedic surgery and bone regeneration.

CN119280456AActive Publication Date: 2025-01-10FUZHOU PORCELAIN TECH CO LTD
View PDF 16 Cites 0 Cited by

Patent Information

Application Number
CN202411414465.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-11
Publication Date
2025-01-10
Estimated Expiration
2044-10-11

AI Technical Summary

Technical Problem

It is difficult to develop a wax-type material with multiple functions such as bioactive, degradable and antibacterial, especially in orthopedic surgery for bone defect repair and hemostasis, and traditional wax materials are non-degradable and have no osteogenic effect.

Method used

By chelating sodium polyphosphate with divalent cations (such as Ca2+, Mg2+ and Sr2+), a pure inorganic wax-like co-doped polyphosphate material CoPPW is prepared, which has hardness, moldability, degradability, antibacterial and hemostatic properties, etc. characteristic.

Benefits of technology

CoPPW materials show excellent ability to promote cell proliferation and osteogenetic differentiation in vitro and in vivo, significantly upregulate osteogenesis-related gene expression, and achieve effective hemostasis and bone regeneration by activating the PI3K/AKT signaling pathway and coagulation cascade pathway.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119280456A_ABST
    Figure CN119280456A_ABST
Patent Text Reader

Abstract

The invention provides a pure inorganic waxy active material and a preparation method and application thereof, and belongs to the technical field of medical materials.The preparation method of the pure inorganic waxy active material comprises the following steps that a sodium polyphosphate solution and a divalent cation solution are mixed and chelated, and waxy co-doped polyphosphate CoPPW is obtained; the divalent cation solution is a solution containing any one, two or three of Ca < 2 + >, Mg < 2 + > and Sr < 2 + >. The pure inorganic waxy active material provided by the invention has certain strength, can be molded and degraded, and has the effects of resisting bacteria, stopping bleeding, repairing bone defects and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of medical materials, and in particular relates to a pure inorganic waxy active material and a preparation method and application thereof. Background Art

[0002] Bone defects refer to situations where the structural integrity of bones is destroyed due to congenital or acquired reasons. There are many causes of bone defects, including acute bone loss, debridement after bone infection, and nonunion or loss of blood supply after radiotherapy or bone tumor resection. Currently, effectively addressing critical bone defects caused by different causes is a major challenge in clinical treatment. Bone, as a hard calcified tissue mainly composed of biomineral phase and organic matrix, is considered difficult to self-repair, so external intervention is required to promote its repair and regeneration. The main approach currently is to use synthetic bone substitutes for repair. Generally speaking, in the field of tissue engineering, materials that replicate the structural, mechanical and biological properties of natural bones are widely used to fill bone defects and promote in situ bone regeneration. Two different types of materials, hard materials and soft biomaterials, have been widely studied, namely bioactive ceramics and gels. Their applications are mainly in the form of particles, porous scaffolds, putties and injectable forms (cements and hydrogels), and deformable forms have attracted more attention due to their ease of handling.

[0003] Sodium polyphosphate (NaPP) is a highly water-soluble inorganic polymer commonly used to prepare polyphosphate solutions. Polyphosphate solutions have a strong chelating ability for multivalent cations in water. Depending on the ionic radius, the addition of multivalent cations will lead to phase separation of polyphosphate solutions, i.e., larger cations (Ba 2+ , Sr 2+ and Ag + ) will cause flocculation, while smaller cations (Ca 2+ Mg 2+ and Zn 2+) can lead to coagulation. Polyphosphate coacervates (CPPs) are defined as isolates consisting of a dense colloidal phase containing mainly long polyphosphate chains chelated with metal ions and an equilibrium liquid phase called supernatant. Polyphosphate coacervate precipitation is the result of electrostatic repulsion and van der Waals attractive interactions with the chelation of multimolecular multivalent cations. Therefore, the coacervation process can be controlled by adjusting the solution pH, precursor concentration, type of multivalent cations, and average degree of polymerization. Polyphosphate coacervates have great potential as guiding matrices for bone repair because they meet the typical requirements of bone regeneration, such as biodegradability to stimulate calcium-phosphate mineralization and leave enough space for new bone formation; osteogenic and osteogenic compatibility to promote bone regeneration; controllable biological properties and injectability by chelating with desired cations. These properties are similar to those of synthetic hydrogels, such as polyethylene glycol (PEG), polyvinyl alcohol (PVA), and polyacrylamide (PAM), which are currently commonly used for bone repair and regeneration. Although there are many studies on the development of CPPs as biomaterials, there are few reports on the use of CPPs as hydrogel-like structures for regeneration, and there are no studies on wax-like structures.

[0004] Although both hydrogels and waxes can be reformed, they are two different types of materials. Hydrogels are dual-phase materials containing a polymer matrix and a medium, mainly water. Wax is a solid material with less internal medium, higher hardness and higher viscosity, and can be used for shielding and as a physical barrier. Typical wax is composed of beeswax, salicylic acid and almond oil. It is completely organic and hydrophobic. Due to the composition and properties of wax, the biological application of wax is limited. Hemostasis in orthopedic surgery is one of its applications. However, wax is non-degradable, has no bioactivity, has no osteogenic effect, and causes more infections. It is still a challenge to develop a new generation of wax-like materials with multiple functions such as bioactivity, degradability and antibacterial. A further question and challenge is whether it is possible to make a wax-like material based on inorganic materials instead of polymers. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a pure inorganic waxy active material and a preparation method and application thereof. The pure inorganic waxy active material has a certain hardness, is moldable, degradable, and has antibacterial, hemostatic, bone defect repairing and other effects.

[0006] The present invention provides a method for preparing a pure inorganic waxy active material, comprising the following steps:

[0007] The sodium polyphosphate solution is mixed with the divalent cation solution to obtain the waxy co-doped polyphosphate CoPPW by chelation;

[0008] The divalent cation solution includes Ca 2+ Mg 2+ and Sr2+ Any one or more solutions.

[0009] Preferably, the concentration of the sodium polyphosphate solution is 0.1-1.5 mol / L, and the average degree of polymerization of the sodium polyphosphate is 10-100.

[0010] Preferably, Ca 2+ The solution is calcium chloride or calcium nitrate solution, including Mg 2+ The solution is magnesium chloride or magnesium nitrate solution, including Sr 2+ The solution is a strontium chloride solution or a strontium nitrate solution, and the total divalent cation concentration in the divalent cation solution is 0.1 to 1.5 mol / L.

[0011] Preferably, the molar ratio of the sodium polyphosphate solution to the total divalent cations in the divalent cation solution is 1:1 to 1:5.

[0012] Preferably, the chelation process is accompanied by stirring, the chelation time is 0.15 to 2 hours, and the chelation temperature is 10 to 60°C.

[0013] The invention provides a waxy co-doped polyphosphate CoPPW prepared by the preparation method, comprising sodium polyphosphate, divalent cations and water; the molar ratio of the divalent cations to the sodium polyphosphate is 5:1 to 1:1; and the water content of the waxy co-doped polyphosphate CoPPW is 25% to 50%.

[0014] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a hemostatic material.

[0015] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a material for repairing bone defects.

[0016] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a reagent for promoting cell proliferation, promoting the expression of osteogenic genes, inducing new bone formation or inducing the formation of extracellular matrix.

[0017] Compared with the prior art, the present invention has the following beneficial effects: the pure inorganic waxy active material provided by the present invention is prepared by chelating sodium polyphosphate with divalent cations, and by limiting the concentration and molar ratio of sodium polyphosphate and divalent cations and selecting the specific type of divalent cations, the prepared pure inorganic waxy active material has a certain hardness, is moldable, degradable, and has antibacterial, hemostatic, bone defect repairing and other effects.

[0018] According to the records of the embodiments of the present invention, the CoPPW prepared by the present invention is ductile and has a fast degradation rate. In vitro studies have shown that compared with beeswax, CoPPW can better promote cell proliferation and osteogenic differentiation, which may be due to the release of polyphosphate, magnesium and strontium ions. The mRNA expression levels of osteogenesis-related genes and the expression of bone-related proteins were analyzed by RT-PCR and transcriptome sequencing, and it was found that CoPPW significantly upregulated the expression of transcription factors BGLPA, OGN, OPN and COL1A1. In addition, the upregulation of the PI3K / AKT signaling pathway confirmed that CoPPW has an osteogenic effect, and the expression of the coagulation cascade pathway showed that CoPPW can effectively stop bleeding. In vivo studies have shown that compared with bone wax, CoPPW is more effective in promoting bone regeneration and hemostasis. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 Schematic diagram of waxy co-doped polyphosphate CoPPW material for repairing bone defects, where (A) is the transformation of the material CoPPW from a hydrogel to a waxy state by chelating sodium polyphosphate with various divalent cations. (B) After implantation in a rabbit model, CoPPW exhibited excellent hemostatic and osteogenesis effects.

[0020] Figure 2 This is the appearance of CoWPP with different compositions. The photo was taken after the sample was pressed once by a punch and then lifted up.

[0021] Figure 3 Performance comparison of CoWPP with different compositions, where (A) is a representative photo of CaSr and MgSr samples; (B) is the dependence of viscosity on shear rate of CoPPW; (C) is the viscosity-shear rate of MgSr2.5 and bone wax measured after 1 day and 4 days; (D) is the SEM-EDX elemental map of the MgSr2.5 sample, showing the distribution of strontium, phosphorus and magnesium elements; (E) is the cumulative release of magnesium, strontium and phosphorus ions in the MgSr2.5 sample; the image shows the dependence of the percentage of weight loss on time; (F) is the applied pressure-stroke curve of bone wax and MgSr2.5 samples (insert image: in vivo blood occlusion test).

[0022] Figure 4 Schematic diagram of the hemostasis test experiment, A shows about 2 mL of CoWPP gel is inserted into the needle, and B shows the mechanical tester applying load to the needle.

[0023] Figure 5 Viscoelastic properties of CoWPP samples showing loss modulus and storage modulus.

[0024] Figure 6 Viscoelastic properties of commercial bone wax.

[0025] Figure 7Viscosity-shear rate of CaMg sample 4 days after preparation.

[0026] Figure 8 The appearance of the CaSr sample 4 days after preparation shows that the sample has solidified.

[0027] Fig. 9 is the cumulative ion concentration of Ca, Mg and P ions released by the CaMg2.5 sample in PBS solution.

[0028] Fig.10 Representative XRD pattern of CoWPP, showing that CaMg and CaSr crystallized after drying at 120 °C to form Ca(H 2 PO 4 ) 2 H 2 O crystal (PDF:96-231-0631); while MgSr2.5 remains amorphous.

[0029] Fig.11 Representative SEM morphology of CoWPP powder after drying at 120 °C for 72 h.

[0030] Fig.12 The in vitro biocompatibility of CoPPW-MSP and bone wax, where (A) is the CCK-8 results in different groups, showing the dependence of OD value on culture days; (B) is EDU staining of the blank group; (C) is EDU staining of high concentration CoPPW-MSP (H-CoPPW); (D) is EDU staining of low concentration CoPPW-MSP (L-CoPPW-MSP); (E) EDU staining of high concentration bone wax (H-bone wax); (F) EDU staining of low concentration bone wax (L-bone wax), where green dots represent dividing and proliferating cells, and blue dots represent normal cell nuclei.

[0031] Fig.13 The osteogenic properties of CoPPW-MSP, where (A) ALP staining of hBMSCs cultured with normal cell culture medium (blank group), L-bone wax group, L-CoPPW-MSP group, H-bone wax group and H-CoPPW-MSP group on day 14; (B) Alizarin Red S staining of the above groups; (C) q-PCR evaluation of gene expression (BGLAP, OGN, OPN and COL1A1) of h-BMSCs cultured with blank group, L-bone wax group, L-CoPPW-MSP group, H-bone wax group and HCoPPW-MSP group, where *p<0.05, **p<0.01, ***p<0.001.

[0032] Fig.14Figure 3 Transcriptome analysis of h-MSC functions and mechanisms regulated by CoPPW-MSP, where (A) is the heat map distribution of the CoPPW-MSP group and the control group, with up-regulated genes marked in red and down-regulated genes marked in blue; (B) is the volcano plot of the CoPPW-MSP group and the control group; (C) is the GO enrichment of genes in the CoPPW-MSP group and the control group; (D) is the KEGG analysis of the CoPPW-MSP group and the control group; (E) is the KEGG metabolic pathway enrichment related genes showing the PI3K-Akt and ECM-receptor interaction signaling pathways (q value < 0.05).

[0033] Fig.15 Comparison of implantation effects between CoPPW-MSP and bone wax groups, where (A) is the micro-CT images of CoPPW-MSP and bone wax groups after 4 and 8 weeks of implantation; (B) is the quantitative analysis of bone volume of CoPPW-MSP and bone wax groups after 4 and 8 weeks of implantation; (C) is the H&E staining of bone defect areas in bone wax and CoPPW-MSP groups after 4 and 8 weeks of implantation; (D) is the Masson staining of bone defect areas in bone wax and CoPPW-MSP groups after 4 and 8 weeks of implantation.

[0034] Fig.16 The hemostatic effects of CoPPW-MSP and bone wax. A: A New Zealand rabbit femur drilling, with a lot of medullary bleeding; b: CoPPW was used to stop bleeding at the drilling site, and after filling, no fresh blood flowed out for 1 minute, and the hemostatic effect was satisfactory. c: A New Zealand rabbit femur drilling, with a lot of medullary bleeding. d: Johnson bone wax was used to stop bleeding at the drilling site, and after filling, no fresh blood flowed out for 1 minute, and CoPPW-MSP and bone wax had the same hemostatic effect. DETAILED DESCRIPTION

[0035] The present invention provides a method for preparing a pure inorganic waxy active material, comprising the following steps: mixing a sodium polyphosphate solution with a divalent cation solution, and chelating to obtain a waxy co-doped polyphosphate CoPPW; the divalent cation solution comprises Ca 2+ Mg 2+ and Sr 2+ A solution of any two of the .

[0036] In the present invention, a sodium polyphosphate solution is first mixed with a divalent cation solution. In the present invention, the concentration of the sodium polyphosphate solution is 0.1 to 1.5 mol / L, preferably 0.3 to 0.8 mol / L, more preferably 0.4 to 0.7 mol / L, and more preferably 0.5 to 0.6 mol / L; in the present invention, the average degree of polymerization of the sodium polyphosphate is preferably 10 to 100, more preferably 20 to 50. In the present invention, the sodium polyphosphate solution is preferably prepared by mixing sodium polyphosphate with water, and the water is preferably deionized water.

[0037] In the present invention, the divalent cation solution includes Ca 2+ Mg 2+ and Sr 2+ Any one or more solutions, including Ca 2+ The solution is calcium chloride or calcium nitrate solution, including Mg 2+ The solution is magnesium chloride or magnesium nitrate solution, including Sr 2+ The solution is a strontium chloride solution or a strontium nitrate solution, and the total divalent cation concentration in the divalent cation solution is preferably 0.1 to 1.5 mol / L, more preferably 0.3 to 0.8 mol / L, and even more preferably 0.5 mol / L; when the divalent cation solution preferably contains Ca 2+ and Mg 2+ When Ca 2+ and Mg 2+ The molar ratio of is preferably 1:5 to 5:1; when the divalent cation solution preferably contains Ca 2+ and Sr 2+ When Ca 2+ and Sr 2+ The molar ratio of is preferably 1:5 to 5:1; when the divalent cation solution preferably contains Mg 2+ and Sr 2+ When Mg 2+ and Sr 2+ The molar ratio of is preferably 1:5 to 5:1; when the divalent cation solution preferably also contains Ca 2+ Mg 2+ and Sr 2+ When Ca 2+ Mg 2+ and Sr 2+ The molar ratio of is (1-5): (5-1): (1-5). In the present invention, Ca 2+ The solution is calcium chloride or calcium nitrate solution, including Mg 2+ The solution is magnesium chloride or magnesium nitrate solution, including Sr 2+ The solution is strontium chloride or strontium nitrate solution.

[0038] In the present invention, after the sodium polyphosphate solution and the divalent cation solution are mixed, chelation is performed, and the chelation process is preferably accompanied by stirring, and the stirring speed is preferably 100-500 rpm; the chelation time is preferably 0.15-2h, and the chelation temperature is preferably 10-60°C. After the chelation is completed, the obtained coagulant will precipitate, and preferably the waxy co-doped polyphosphate CoPPW is obtained by solid-liquid separation.

[0039] The present invention also provides a waxy co-doped polyphosphate CoPPW prepared by the preparation method, comprising sodium polyphosphate, divalent cations and water; the molar ratio of the divalent cations to the sodium polyphosphate is preferably 5:1 to 1:1; the water content of the waxy co-doped polyphosphate CoPPW is preferably 25% to 50%.

[0040] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a hemostatic material.

[0041] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a material for repairing bone defects.

[0042] The present invention also provides the use of the waxy co-doped polyphosphate CoPPW in preparing a reagent for promoting cell proliferation, promoting the expression of osteogenic genes, inducing new bone formation or inducing the formation of extracellular matrix.

[0043] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0044] Example

[0045] Average degree of polymerization Commercial sodium polyphosphate (NaPP) with a concentration of 20 (Thermo Fisher Scientific Inc., USA) was used as a polyphosphate precursor. NaPP powder was dissolved in deionized water to prepare a NaPP solution with a concentration of 0.5 mol / L. Calcium chloride (CaCl2, Thermo Fisher Scientific Inc., USA), magnesium chloride (MgCl2, Sigma-Aldrich, USA) and strontium nitrate (Sr(NO 3 ) 2 , Sigma-Aldrich, USA) as divalent cations (M 2+ ) chelating source. Two of calcium chloride, magnesium chloride and strontium nitrate were dissolved in deionized water to prepare cationic solutions of different concentrations. The cationic solutions were added to the NaPP solution and stirred for 0.5 h until the coagulants precipitated at the bottom of the solution. 2+ / P) molar ratio, see Table 1. Among them, for the dual ion chelation, three different molar ratios were prepared M A M B 3.

[0046] M A M B 2.5 and M A M B 1.5.

[0047] Table 1 Sample composition and water content of waxy co-doped polyphosphate CoPPW

[0048]

[0049]

[0050] Material Characterization:

[0051] Chemical composition and water content of CoPPW:

[0052] The CoPPW prepared above was washed with deionized water and dried in an oven at 120° for 72 h. The dry powder was measured by an x-ray diffractometer (XRD, D8advance, Bruker, USA) in the range of 10° to 80°, with a scanning step of 0.2 s / step and a step size of 0.02°. Its microstructure and element distribution were analyzed using a scanning electron microscope (SEM, Merlin, Zeiss, Germany) equipped with energy dispersive x-ray spectroscopy (EDS). The moisture content of CoPPW was calculated using the formula: Moisture content (%) = (W 湿 -W 干 ) / W 湿 × 100%, where W 湿 and W 干 are the weights of wet and dry CoPPW, respectively.

[0053] The results are as follows Figure 2 As shown, the image of the newly synthesized CoPPW is Figure 2 and Figure 3 As shown in A in Figure 1, it can be seen that the CaSr sample presents a white opaque appearance, while the CaMg and MgSr samples present a grayish white appearance. The MgSr sample is more translucent than the other samples. The elemental composition was analyzed using SEM-EDS, as shown in Figure 1. Figure 3 As shown in D in Figure 1, the EDS elemental map of the dried MgSr2.5 shows a uniform distribution of Mg, Sr, and P elements. The experimentally obtained molar ratio of cations to phosphorus (Mⅱ / P) is lower than the theoretical value, indicating that some cations were not chelated to NaPP during the preparation process but remained in the supernatant. As shown in Table 1, the water percentage in CoPPW is between 30 wt% and 43 wt%.

[0054] The concentration of divalent cations plays an important role in determining the chelating capacity. In divalent cation-phosphate systems, the occupancy of metal ions depends on the concentration of divalent cations; at low concentrations, cations are trapped inside the polyphosphate cages, whereas at higher concentrations, the cages are saturated and the cations are therefore chelated to the external polyphosphate chains15,16. Therefore, the precipitation of the coacervate depends on van der Waals attractions and electrostatic repulsion. The critical concentration (M*) that leads to precipitation is determined by the concentration and the average degree of polymerization of NaPP.

[0055] Rheological properties of CoPPW:

[0056] The rheological properties of CoPPW were evaluated using a rheometer (Discovery HR10, TA instruments, USA). -1 The dependence of viscosity on shear rate was measured in the range of 1.5 % to 2.5 % (-1.5 % to 1.5 % ) / min. The viscoelastic properties of the coacervates were determined by the storage modulus (G′) and the loss modulus (G″) in the frequency range of 0.1-100 Hz. To investigate the influence of temperature, rheological measurements were performed at 25° and 37°. Rheological tests were performed one hour after the coacervate preparation. All samples were measured after 1 and 4 days to determine the viscosity evolution over time.

[0057] The effect of divalent cation chelation on the rheological properties of CoPPW was investigated in a dynamic frequency sweep. All CoPPWs exhibited shear-thinning behavior, with the viscosity decreasing with increasing shear rate ( Figure 3 B). Except for the MgSr3 sample, the viscosity of the CaSr sample is higher than that of the other samples. The viscoelastic behavior of CoPPW chelated with different types and amounts of cations is different. In the MgSr3 and MgSr2.5 samples, the loss modulus (G") is higher than the storage modulus (G'), and both (G") and (G') increase with increasing frequency, indicating that CoPPW exhibits more viscous fluid properties. In the CaSr3 and CaMg samples, (G') is higher than (G"), indicating solid-like behavior. Fig. 9 As shown in Figure 2, the viscosity changes of CoPPW samples were measured after 1 day and 4 days. It can be seen that after 4 days, only the CaMg sample and the MgSr2.5 sample are moldable, while the other samples are solidified (e.g. Fig.10 Specifically, the viscosity of the MgSr2.5 sample and bone wax is compared as shown in Figure 3 As shown in C. After 1 day, MgSr2.5 is still in a liquid gel structure with a viscosity lower than that of wax; while after 4 days, MgSr2.5 becomes solid and can be shaped.

[0058] CoPPW has an extremely high viscosity, which is consistent with its waxy appearance. This is probably due to a multivariate effect caused by the simultaneous chelation of dual cations. In polyelectrolyte solutions, the addition of cations has opposite effects on viscosity. At low concentrations, cation chelation reduces viscosity due to chain breakage caused by charge screening effects, while at high concentrations, cation chelation increases viscosity due to enhanced interactions between chains. The water content of CoPPW ranged from 32% to 43%, indicating that the samples were highly concentrated. Therefore, the higher the cation content, the higher the viscosity. MgSr and CaSr also have higher viscosities than CaMg, which may be due to the fact that Sr 2+ More effective in cross-linking polyphosphate chains.

[0059] In vitro degradation behavior and ion release:

[0060] The in vitro degradation behavior of CoPPW was evaluated by immersing the samples in PBS solution at a temperature of 37°C. The ratio of PBS volume (mL) to sample weight (g) was 10mL:1g. On days 1, 7, 14, 21, 28, 35, and 46, the PBS solution was removed and the weight loss was measured. The percentage of weight loss was determined by the ratio of (original weight - residual weight) to the original weight. The release of ions was also studied. At each time interval, 1 mL of the supernatant was taken and replaced with fresh PBS solution. The collected supernatant was analyzed for Sr by inductively coupled optical emission spectrometry (PerkinElmer, Inc., USA). 2+ Mg 2+ and P 4+ Cumulative concentration of ion release. Solutions were collected on days 1, 2, 4, 6, 8, 14, and 21.

[0061] The degradation of MgSr2.5 and CaMg2.5 was studied by immersing the samples in PBS solution. The weight loss percentage of MgSr2.5 over time is shown in Figure 3 As shown in Figure E. In the first week, the MgSr2.5 sample absorbed water and gained 10% weight, followed by a gradual weight loss over the next week. Significant weight loss was observed between days 14 and 28, with a 37% weight loss on day 28. At the end of the 46-day measurement period, the weight loss of MgSr2.5 was approximately 41%. In addition, the Mg released from MgSr2.5 was analyzed using ICP-OES. 2+ , Sr 2+ and P 5+ ion concentration. Consistent with the weight loss results, the ions released from MgSr2.5 were released slowly within the first week without a sudden release. 5+ The release of ions was higher than that of divalent cations, indicating that a higher Mⅱ / P ratio existed in the remaining MgSr2.5. After 21 days, Mg 2+, Sr 2+ and P 5+ The cumulative release concentrations of ions were 2.57, 2.34, and 7.89×10 3 mg·L -1 . CPP is easily degraded due to the presence of water, and the POP bond dissociates to form trimetaphosphate and orthophosphate. The presence of cations catalyzes this process by neutralizing the charge on the chain. In previous studies, CPP remained stable for the first two days and then rapidly degraded, resulting in significant weight loss and abrupt release of ions. In contrast, in the present invention, MgSr2.5 absorbed water in the first week and degraded slowly over the next week, indicating its potential for long-term use in vivo. Sr 2+ and Mg 2+ The slow dissolution of ions may be the reason for the slow degradation of MgSr2.5.

[0062] Hemostatic ability evaluation:

[0063] To compare the hemostatic ability of CoPPW with commercial bone wax (BBraun Surgical SA, Spain), the maximum force required to induce leakage was measured using a universal mechanical testing machine (Autograph AGS-H; Shimadzu, Japan). Bone wax is composed of 75% beeswax, 15% paraffin, and 10% isopropyl palmitate. Figure 4 Specifically, about 2mL of sample is inserted into the syringe and 5mL of water is injected. Then, the force is applied to the syringe until the water drips down and the test stops.

[0064] The results are as follows Figure 3 As shown in F in Figure 2, the sample was pushed while the load was applied until the maximum pressure was reached, after which water began to leak and the pressure dropped. The maximum pressure applied to MgSr2.5 to trigger water leakage was approximately twice that of wax, indicating that the MgSr2.5 sample had excellent occlusion capacity. Figure 3 The inserted image in F shows the in vivo blood occlusion test, where it can be seen that after applying CoPPW glue to the drilling site and waiting for 1 minute, no fresh blood flowed out.

[0065] Biocompatibility evaluation of CoPPW

[0066] In the present invention, considering the viscosity and potential ion effects, MgSr2.5-CoPPW (magnesium strontium polyphosphate, CoPPW-MSP) was selected to continue the biological evaluation.

[0067] Human bone marrow mesenchymal stem cells (h-BMSC; ScienCell, #7500, USA) were cultured in h-MSC basal medium (Cyagen, HUXMA-90,011, China) containing 10% fetal bovine serum (Cyagen, HUXMA-90,011, China), 1% antibiotics (Cyagen, HUXMA-90,011, China), 37°C, 95% air and 5% CO 2 1 g MgSr2.5-CoPPW was added to 10 ml cell culture medium and incubated at 37 °C with 95% air and 5% CO 2 Mix for 24 hours. Collect the supernatant and filter it three times with a 0.22 μm filter membrane (Merck Millipore, USA) to obtain a biological material extract. Finally, the supernatant was diluted to 5 times and 10 times with a cell culture medium to obtain a high-concentration and low-concentration biological material extract culture medium, respectively.

[0068] The effects of the biomaterial MgSr2.5-CoPPW on the proliferation and cytotoxicity of h-MSCs were evaluated by CCK-8 (CCK-8, purchased from Dojindo, Japan). 3 Cells / well were seeded in a 96-well plate and cultured with h-MSC culture medium and MgSr2.5-CoPPW extraction medium, respectively. After 1d, 2d, 3d, 5d, and 7d of culture, CCK-8 solution was added to the wells for 2h. The absorbance of each well was measured at 450nm. h-MSCs were cultured at 1.5×10 5 The cells were seeded in a 6-well plate at a density of 1.54 cells / well. The blank group was cultured with normal cell culture medium, and the control group and experimental group were cultured with high and low concentration extracts. On the 7th day of culture, edu (5-ethynyl-2'-deoxyuridine) staining was performed using an EDU kit (Biyuntian, China) according to the manufacturer's protocol, and photos were taken.

[0069] h-MSCs were cultured at 2×10 5 Cells / well were seeded in 12-well plates and stimulated with cell culture medium and biomaterial extracts for 14 days. Total RNA of BMSCs was extracted using Trizol reagent (Invitrogen, California, USA). One-step SYBR primescript qPCR kit (TaKaRa Bio, Otsu, Japan) was used to synthesize cDNA according to the manufacturer's instructions. Quantitative real-time PCR (qPCR) was performed using SYBR Premix Ex Taq (TaKaRa) in a Bio-Rad CFX96 real-time PCR system using thermal cycling conditions.

[0070] The cDNA fragment was amplified by real-time PCR using the following specific primers.

[0071] Table 2 Specific primer sequences

[0072]

[0073]

[0074] The results are as follows Fig.12 As shown in A, after culturing h-BMScs for 1, 2, 3, 5, and 7 days, the optical density (OD) values ​​of bone wax and CoPPW-MSP gradually increased with the culture time, indicating that the number of living cells increased. After the 5th day, the cell viability of the low-concentration and high-concentration CoPPW-MSP groups was higher than that of the bone wax group and the blank group. To further confirm the CCK-8 results, on the 7th day of h-BMSC culture, the different concentration treatment groups were stained with edu (5-ethynyl-2'-deoxyuridine) ( Fig.12 In the low-concentration CoPPW-MSP group, the number of mesenchymal stem cells that replicated and divided was significantly higher than that in the other groups. The cell proliferation rate in the low-concentration CoPPW-MSP group was 29.3% ( Fig.12 A in the figure was higher than that in the blank group (20.8%) and the low concentration bone wax group (21.7%).

[0075] Alizarin red staining and alkaline phosphatase staining

[0076] h-BMSCs were cultured at 2×10 5 Cells / well were seeded in 6-well plates and treated with cell culture medium containing or without biomaterial extracts. After 14 days of culture, calcium deposition of h-BMSCs was detected using Alizarin Red staining (Cyagen, HUXMA-90,021, China). Mineralized particles were observed using an inverted microscope (Nikon, Japan). After 14 days of culture in MSCs treated with cell culture medium containing or without biomaterial extracts, alkaline phosphatase staining (Beyotime, China) was performed on all groups and photographed under a microscope (Nikon, Japan).

[0077] Ions released from CoPPW-MSP materials can stimulate cell proliferation and replication at specific concentrations, and there was no significant difference between CoPPW-MSP and bone wax in the first 3 days ( Fig.12 A), which is attributed to Mg 2+ and Sr 2+ Slow release of ions (eg Figure 3 After 5 days, the Mg released by CoPPW-MSP 2+ and Sr 2+ Ions increase, promoting cell proliferation and division.

[0078] In vitro osteogenic properties of CoPPW-MSP

[0079] After stimulating h-BMScs with the extract medium for 14 days, the osteogenic properties induced by CoPPW-MSP and bone wax were further investigated by alkaline phosphatase (ALP) and Alizarin Red S staining. Fig.13 As shown in Figure A, there were more ALP-positive cells in the high- and low-concentration CoPPW-MSP groups compared with the bone wax group and the blank group. In addition, the ALP-positive rate in the high-concentration CoPPW-MSP group was higher than that in the low-concentration CoPPW-MSP group. Fig.13 As shown in Figure 5B, calcium deposition as an indicator of late osteogenesis was evaluated by alizarin red staining of the h-MSCs extracellular matrix. Compared with the blank group and the bone wax group, the calcium nodule staining in the CoPPW-MSP group was more intense and obvious. In addition, increasing the concentration of CoPPW-MSP further promoted the formation of calcium nodules. Quantitative real-time polymerase chain reaction (q-PCR) was used to explore the potential osteogenic mechanism of CoPPW-MSP at the gene expression level. Fig.13 As shown in Figure C, the gene expressions of osteoglycin (OGN), osteopontin (OPN), type I collagen α1 (col1a1), and osteocalcin (BGLAP) in the CoPPW-MSP group were significantly higher than those in the control group and the bone wax group. In addition, high concentrations of CoPPW-MSP showed the most significant effect on the expression of these osteogenesis-related genes (including OGN, OPN, COL1A1, and BGLAP), indicating that CoPPW-MSP has excellent osteogenesis ability. The typical bone formation process includes cell proliferation, extracellular maturation, and mineralization. ALP activity and the formation of mineralized nodules were used to evaluate the early stages of osteogenesis. In the present invention, CoPPW may promote osteogenic differentiation and mineralization because it exhibits a better expression effect on osteogenesis-related genes ( Fig.13 C in this case). This may be due to the fact that Sr 2+ and Mg 2+ Ion release. The osteogenic and angiogenic abilities of strontium-doped calcium polyphosphate bioceramics (Sr-CaPP) have been studied, however, their hardness does not meet the clinical requirements of waxy and sticky properties. In the present invention, CoPPW-MSP exhibits excellent osteogenic ability while maintaining excellent waxy properties, indicating that it has good application prospects in bone repair and regeneration.

[0080] Potential mechanisms of osteogenesis and coagulation in CoPPW-MSP

[0081] Transcriptome sequencing and data analysis

[0082] The samples were divided into three groups: blank group (undifferentiated h-BMSCs), bone wax group, and CoPPW-MSP group. The h-BMSCs in the three groups were cultured in a 6-well Trans well plate for 14 days to allow stimulated differentiation of h-BMSCs. There were three replicates in each group. The cells were detached using trypsin, suspended to remove the supernatant, and stored in liquid nitrogen. RNA sequencing analysis was performed at the Beijing Genomics Institute. In addition, network and pathway analysis was performed using the analysis software IPA.

[0083] h-BMSCs were further used for transcriptome sequencing to explore the potential osteogenesis induced by CoPPW-MSP. The differentially expressed genes of h-BMSCs were revealed in the heat map ( Fig.14 Compared with the bone wax group, the total number of differentially expressed genes (p value < 0.05 and |log2 fold change| > 0) was 3226, including 1881 up-regulated genes and 1345 down-regulated genes (e.g. Fig.14 GO enrichment was applied to analyze these differentially expressed genes, most of which were involved in osteogenesis and extracellular matrix, including extracellular matrix and structural organization, collagen metabolism, cell adhesion molecule binding, growth factor binding, and collagen binding ( Fig.14 Based on these significantly differentially expressed genes, the KEGG metabolic pathway was used to analyze key osteogenic signaling pathways, such as Fig.14 As shown in D. KEGG signaling pathway analysis showed that the PI3K / Akt signaling pathway and the ECM receptor interaction signaling pathway were highly enriched and played an important role in promoting the osteogenic differentiation of h-BMSCs. The PI3K / Akt signaling pathway is an important lipid kinase activation pathway that significantly regulates the osteogenic differentiation, proliferation and apoptosis of MSCs. AKt phosphorylation can upregulate the Runx2 gene and induce the expression of bone repair and reconstruction related genes, such as BGLAP, COL1, OPN and ALP26. In the present invention, gene sequencing ( Fig.14 E) shows that CoPPW-MSP effectively activates the PI3K / Akt signaling pathway, which further affects the mTOR signaling pathway through REDD1 overexpression. The activated AKT-mTOR signaling pathway promotes MSCs differentiation into osteoblasts and increases the mRNA translation rate, thereby increasing cellular protein synthesis. In addition, overexpression of the downstream target protein p53, activated by AKT, can promote cell proliferation and cell cycle progression ( Fig.14 E) Release of Mg from CoPPW-MSP 2+ and Sr 2+ Ions enhance the activation of the PI3K / Akt signaling pathway, thereby upregulating the expression of osteogenic genes and proteins and promoting osteogenesis. At the same time, CoPPW-MSP also activates the ECM-receptor interaction signaling pathway ( Fig.14 D in ). This signaling pathway affects collagen metabolism and synthesis in bone and plays an important role in regulating cell adhesion, thereby promoting the formation of extracellular matrix. The upregulated expression of the ECM-receptor interaction signaling pathway is consistent with the significant increase in type I collagen expression in CoPPW-MSP by QT-PCR ( Fig.13 On the other hand, CoPPW-MSP activated complement and coagulation cascade signaling pathways ( Fig.14 E), which plays an important role in subsequent cellular responses affecting anti-inflammatory and tissue repair. In the coagulation cascade of CoPPW-MSP, the expression of PAR1, PAR3 and PAR4 is upregulated due to activated coagulation factor VIII and coagulation factor X, leading to the release of anti-inflammatory mediators and increased endothelial permeability. Polyp has been shown to accelerate blood coagulation, with increased thrombin generation in the case of polyp activated factor Xι32. In addition, polyp slows fibrinolysis because it modulates the fibrin clot structure, making it more resistant to fibrinolysis.

[0084] In vivo studies: rabbit femoral defect model surgical procedure

[0085] Based on the method reported in references (Sun, Y., Helmholz, H. & R.Surgical Classification for Preclinical Rat Femoral Bone Defect Model: StandardizationBased on Systematic Review, Anatomical Analysis and Virtual Surgery. Bioengineering 9, (2022).) A modified femoral defect model was constructed to evaluate bone repair in rabbits. First, rabbits were anesthetized by intravenous injection of 1% pentobarbital (50 mg / kg) via the auricular vein. After the surgical area was shaved and disinfected, the animal was placed in a fixed position on the left side of the operating table. Next, a 5-mm incision was made around the femoral shaft. After the superficial and deep fascia were dissected, the bulge was identified as the drilling target. A 5-mm-diameter Kirschner wire was drilled into the target area continuously to form a cavity defect with a diameter of 5 mm and a depth of 10 mm from the lateral to the medial side in a direction perpendicular to the longitudinal axis of the femoral shaft. Critical defect size was created in 12 rabbits. The left diaphysis received bone wax for the cavity defect, while CoPPW-MSPs were implanted for the cavity defect in the right diaphysis. All procedures strictly adhered to aseptic principles, and each subject received intramuscular antibiotics on postoperative day 1. The rabbits were allowed to move freely after surgery without immobilization. At 4 and 8 weeks after surgery, the rabbits were sacrificed and bilateral femurs were collected for evaluation.

[0086] Micro-computed tomography (micro-CT) evaluation

[0087] In order to evaluate the bone volume and density under the specific Hu value, the lateral area of ​​the femur was scanned using micro-CT (Siemens, Germany). The resolution of micro-CT scanning was 10.3 microns, the voltage was 70 kilovolts, and the current was 400 milliamperes. The image obtained was used to construct the 3D model of the femur using Dslicer software (Inveon Research Workplace software). Bone volume was calculated by identifying the region of interest with the Hu signal ranging from 700 to 2100. The bone volume / total bone volume (BV / TV) ratio was then calculated using the bone volume of the selected region. Histological analysis was performed by decalcification of the femur sample, and a rotary microtome (RM2255, Leica, Germany) was used to cut into 4 micron thick paraffin sections. The sections were then stained with hematoxylin-eosin (HE) (607317-0100 & E607321-0100, SangonBiotech, China) and Masson's trichrome (G1340, Solarbio, China) and examined under a microscope (Ci-S, Nikon, Japan) to detect bone formation.

[0088] Fig.15 Figure A shows μ-CT images of bone wax and CoPPW-MSP at 4 and 8 weeks after implantation. At week 4, newly formed bone was evident in the CoPPW-MSP group, whereas the femoral defect in the bone wax group was still hollow. Over time, the femoral defect gradually healed, and the newly formed tissue partially filled the defect site. By week 8, the femoral defect in the CoPPW-MSP group was no longer visible, whereas in the bone wax group, only a small amount of new bone tissue was observed at the edge of the defect. Quantitative micro-CT analysis of bone volume is shown in Figure 2. Fig.15 As shown in Figure B, the bone volume density (BV / TV) of the CoPPW-MSP group was significantly higher than that of the bone wax group at 4 weeks (p=0.0055) and 8 weeks (p=0.0151) after implantation. Histological analysis was performed using hematoxylin-eosin (H&E) staining and Masson staining to evaluate the extent of defect recovery ( Fig.15 (C, D). In the bone wax group, the defect was still hollow 4 weeks after implantation, and only a small amount of fibrous tissue was formed below the defect by week 8. In contrast, the CoPPW-MSP group showed more newly formed bone toward the defect center at week 4, and almost all the defects were filled with newly formed bone by week 8, indicating that CoPPW-MSP has better bone regeneration ability.

[0089] To observe blood occlusion, the femur of New Zealand white rabbits was drilled, resulting in a large amount of blood flowing out of the defect. CoPPW-MSP and bone wax were used to stop bleeding, respectively. Both groups showed good occlusion effects ( Fig.16 ). In plastic surgery, it is challenging to stop bleeding at the bone defect. Usually, it is necessary to fill the defect with a bioadhesive wax material such as beeswax to physically close the defect. However, current wax materials cannot induce new bone formation. The pure inorganic wax material CoPPW provided by the present invention can quickly stop bleeding and induce bone formation at the same time.

[0090] In summary, the present invention has developed for the first time a pure inorganic waxy material based on an ion-regulated polyphosphate formula; by controlling the type and concentration of ions, the viscosity and modulus of CoPPW can be adjusted from a gel-like state to a wax-like state with fluidity and desired formability. In vitro studies have confirmed that CoPPW has good biocompatibility and can promote cell proliferation. The synergistic release of magnesium ions and strontium ions can effectively promote the expression of osteogenic genes, and show regulation of the PI3K / AKT signaling pathway and ECM-receptor interactions, thereby inducing extracellular matrix and new bone formation. At the same time, CoPPW can activate complement and coagulation cascade signaling pathways to exert a hemostatic function. The New Zealand white rabbit proximal femur defect model verified its hemostatic effect, which is comparable to the hemostatic effect of existing bone wax. In addition to hemostasis, the CoPPW provided by the present invention also promotes bone regeneration by self-degradation in vivo.

[0091] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a pure inorganic waxy active material, characterized in that: The following steps are involved: The sodium polyphosphate solution is mixed with the divalent cation solution to obtain the waxy co-doped polyphosphate CoPPW by chelation; The divalent cation solution includes Ca 2+ Mg 2+ and Sr 2+ Any one or more solutions.

2. The preparation method according to claim 1, characterized in that: The concentration of the sodium polyphosphate solution is 0.1-1.5 mol / L, and the average polymerization degree of the sodium polyphosphate is 10-100.

3. The preparation method according to claim 1, characterized in that: Including Ca 2+ The solution is calcium chloride or calcium nitrate solution, including Mg 2+ The solution is magnesium chloride or magnesium nitrate solution, including Sr 2+ The solution is a strontium chloride solution or a strontium nitrate solution, and the total divalent cation concentration in the divalent cation solution is 0.1 to 1.5 mol / L.

4. The preparation method according to claim 3, characterized in that: The molar ratio of the sodium polyphosphate solution to the total divalent cations in the divalent cation solution is 1:1 to 1:

5.

5. The preparation method according to claim 1, characterized in that: The chelation process is accompanied by stirring, the chelation time is 0.15 to 2 hours, and the chelation temperature is 10 to 60°C.

6. The waxy co-doped polyphosphate CoPPW prepared by the preparation method according to any one of claims 1 to 5, characterized in that: It comprises sodium polyphosphate, divalent cations and water; the molar ratio of the divalent cations to the sodium polyphosphate is 5:1 to 1:1; and the water content of the waxy co-doped polyphosphate CoPPW is 25% to 50%.

7. Use of the waxy co-doped polyphosphate CoPPW according to claim 6 in the preparation of hemostatic materials.

8. Use of the waxy co-doped polyphosphate CoPPW according to claim 6 in preparing a material for repairing bone defects.

9. Use of the waxy co-doped polyphosphate CoPPW according to claim 6 in the preparation of an agent for promoting cell proliferation, promoting the expression of osteogenic genes, inducing new bone formation or inducing the formation of extracellular matrix.

Citation Information

Patent Citations

  • Doped bone repairing material and preparation method thereof

    CN101444640A

  • Injectable composite material capable of promoting bone regeneration and repair and preparation method thereof

    CN101695584A

  • Bone graft material with plasticity and capability of enhancing and accelerating bone formation and preparation method thereof

    CN103961740A

  • Method for preparing high specific surface calcium polyphosphate microspheres

    CN103979518A

  • Preparation method and application of long-chain polyphosphate

    CN118546844A